Freedom for rent. Informal housing market of Caracas - Briceño León, Roberto (Universidad del Rosario, 2010)
For years it was believed that in Caracas an informal rental housing market did not exist. A survey (n:832) in seven informal areas shows the opposite. The article analyzes the socio-legal aspects and characteristics of the market: the negotiated property, the rent, the actors and the norms that regulate the market. It is concluded that the Venezuelan State, with its controls and social policies, has become the principal promoter of the informal rental market and that because of the freedom to rent, the poor are the real estate agents that contribute most to meeting the increasing demand for housing.